Enhancing Digital Video Streaming Through Blockchain and Smart Contracts - Yogie Ajie Pratama (Komunitas Dosen Indonesia, 2025)
The rapid advancement of digital technologies has catalyzed significant growth in video-on-demand (VOD) services, which now dominate the content distribution landscape. However, conventional digital streaming platforms still rely heavily on third-party intermediaries for copyright registration and payment processing, often leading to elevated transaction costs, data privacy concerns, and revenue fragmentation for content creators. This paper proposes a blockchain-based digital video streaming architecture that leverages Smart Contracts and Decentralized Applications (DApps) to streamline the content distribution process, enhance transparency, and eliminate the need for centralized control. Utilizing the immutable, decentralized, and cryptographically secure nature of blockchain technology, Smart Contracts facilitate automated, direct transactions between content providers and consumers. The proposed system adopts a peer-to-peer model incorporating blockchain platforms such as Ethereum and Vexanium to implement contract enforcement, ownership verification, and micropayment mechanisms. Moreover, it introduces a crypto-based incentive model wherein users contribute bandwidth and computational resources in exchange for digital tokens, thereby promoting a self-sustaining and decentralized content delivery ecosystem. By shifting content ownership validation and access control to the blockchain layer, the model reduces operational overhead, enhances data integrity, and mitigates the risks associated with content piracy and unauthorized access. This study demonstrates how blockchain integration in streaming infrastructure fosters greater equity, security, and scalability, offering a transformative framework for the future of digital media distribution. The research contributes to the evolving discourse on decentralized systems by illustrating the technical feasibility and socio-economic benefits of blockchain-enabled video streaming services